Amoxicillin induced toxic epidermal necrolysis (TEN): a case report - Patel, Jaimin B.; Agrawal, Palak; Soitawala, Sunil; Sattigeri, Bhagya Manoj (International Journal of Research in Medical Sciences, 2017)
Each year many patients are hospitalized due to adverse drug reactions. Adverse reactions are the recognized hazards of drug therapy and they can occur with any class of drugs and many studies revealed that the incidence is more in case of antibiotics. Amoxicillin is a broad spectrum, bactericidal, beta lactam antibiotic, commonly used to combat various infections. Penicillin group of drugs are known to cause cutaneous drug eruptions especially in pediatric population. Most of the time, these eruptions are mild in nature, however, sometimes they represent the early manifestation of rare, severe drug-induced cutaneous reactions, such as Stevens-Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN). Toxic Epidermal Necrolysis (TEN) is a rare, life threatening dermatological disorder that is usually induced by medications. Seventy percent of the cases of TEN are drug induced, most commonly implicated drugs being anticonvulsants, antibiotics and Non-Steroidal Anti-Inflammatory Drugs (NSAIDS). Here, we report a case of toxic epidermal necrolysis induced by amoxicillin in a 16 year old female patient. Rigorous treatment with systemic corticosteroids and immunoglobulins helped in recovery of the patient. The case is being reported to emphasize the need for efficient pharmacovigilance in order to motivate adverse drug reaction reporting so as to gather more and more data regarding adverse drug reactions. Through this report, we also seek the support of everyone concerned to detect and, if possible, prevent adverse reactions to drugs.